When Scientific Software Meets Software Engineering. - Leroy, Dorian; Sallou, June; Bourcier, Johann; Combemale, Benoit (Computer (00189162), 2021)
We investigate the different levels of abstraction, linked to the diverse artifacts of the scientific software development process, that a software language can propose and the validation and verification facilities associated with the corresponding level of abstraction the language can provide to the user.